Electrochemical studies in anhydrous formic acid - Pinfold, T A; Pinfold, Thomas Arthur (Department of Chemistry, 2017)
Although anhydrous formic acid exhibits all the properties required by a solvent for ideal polarographic characteristics, no study of the dropping mercury electrode in this medium has hitherto been described. Formic acid besides having a high dielectric constant (56.1 at. 25ᵒC) and considerable ionizing properties, also exhibits a strong solvent action upon many organic compounds. Furthermore, it has been shown by Pleskov (2) to be a solvent with small complexing power, a feature which enhances its value for the examination of ions which are normally hydrated in aqueous solution. The above author also showed that the standard electrode potentials in formic acid, of the elements he studied, differed little from the values found in aqueous solution. Exceptional behaviour was shown by zinc and cadmium the potentials of which were displaced to more positive values. This shift was attributed to hydration of ions in aqueous solution as opposed to the absence of solvation in formic acid. The remaining electrochemical investigations in anhydrous formic acid have been confined to conductance measurements, the measurement of transport numbers and potentiometric titrations. The conductance measurements were made almost entirely by Schlesinger and his co-workers. The conductivities of ammonium, alkali and alkaline earth formates as well as hydrogen chloride solutions in anhydrous formic acid were measured together with the behaviour of mixtures of two salts containing a common ion. More recently, Lange has measured the conductance of potassium chloride in this solvent. Schlesinger and Bunting obtained values for the transference numbers of the formates of sodium potassium and calcium in formic acid. The outcome of these experiments was that anhydrous formic acid should be considered to be a highly acidic solvent; hydrogen chloride was, for example, found to be incompletely ionised, while salts such as the alkali and alkaline earth formates, which are bases in anhydrous formic acid, were highly ionized. A number of workers (10-15) have employed anhydrous formic acid as the medium for potentiometric titrations and conclude that "formic acid is more like water, then is such a solvent as acetic acid, in that solutions of salts give cryoscopic and conductivity values which correspond to extensive dissociation with respect to acidity and basicity, however, formic acid differs greatly from water, and solutions in it are even more deserving of the term superacid than those acetic acid solutions in which the pioneer work on the potentiometric investigation of strongly acid solvents was done". In view of the interesting properties shown by anhydrous formic acid, it was decided to investigate the electrochemical properties of this solvent, paying particular attention to its suitability for the reduction of electroreducible ions at a dropping mercury cathode.